1997
DOI: 10.1021/jm9700833
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Analogs of 2-Methoxyestradiol with Enhanced Inhibitory Effects on Tubulin Polymerization and Cancer Cell Growth

Abstract: A new series of estradiol analogs was synthesized in an attempt to improve on the anticancer activity of 2-methoxyestradiol, a naturally occurring mammalian tubulin polymerization inhibitor. The compounds were evaluated as inhibitors of tubulin polymerization and the binding of [3H]colchicine to tubulin, as well as for in vitro cytotoxicity in human cancer cell cultures. Overall, the most potent of the new compounds were 2-(2',2',2'-trifluoroethoxy)-6-oximinoestradiol, 2-ethoxy-6-oximinoestradiol, and 2-ethoxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 46 publications
4
70
0
2
Order By: Relevance
“…The syntheses of compounds 1, 2, 4, 9 to 12, 26 (Cushman et al, 1995), 5, 18 (Cushman et al, 1997), 21, 22 (Verdier-Pinard et al, 2000), and 23 to 31 have been described previously. Compounds 3, 16, 18, 19, and 34-39 were purchased from Sigma (St. Louis, MO).…”
Section: Compoundsmentioning
confidence: 99%
See 3 more Smart Citations
“…The syntheses of compounds 1, 2, 4, 9 to 12, 26 (Cushman et al, 1995), 5, 18 (Cushman et al, 1997), 21, 22 (Verdier-Pinard et al, 2000), and 23 to 31 have been described previously. Compounds 3, 16, 18, 19, and 34-39 were purchased from Sigma (St. Louis, MO).…”
Section: Compoundsmentioning
confidence: 99%
“…Synthesis of 17␤-Acetoxy-2-ethoxy-3-hydroxy-6-hydroximinoestra-1,3,5(10)-triene (8). A solution of compound 43 (Cushman et al, 1997) (800 mg, 1.93 mmol) in pyridine (12 ml) was treated with hydroxylamine hydrochloride (1.07 g, 15.4 mmol). The resulting mixture was stirred and heated at 100°C for 30 min.…”
Section: Synthesis Of 2-formylestradiol (42)mentioning
confidence: 99%
See 2 more Smart Citations
“…1, 2), has strong antiproliferative and apoptotic actions in a number of cultured cancer cell lines when it was present at pharmacologic concentrations (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Among many of the human cancer cell lines tested thus far, several human breast cancer cell lines were found to be highly sensitive to the antiproliferative actions of 2-MeO-E 2 in vitro (3,4,12). Additional studies also showed that 2-MeO-E 2 inhibited the growth of human breast cancer cells when they were transplanted into immune-suppressed mice (10).…”
Section: Introductionmentioning
confidence: 99%